The Little Data Book 2006 - World Bank (Washington, DC, 2012)
The Little Data Book (LDB) 2006 is a pocket edition of World Development Indicators (WDI) 2006. It is intended as a quick reference for users of WDI 2006 book and CD-ROM and WDI online, electronic subscription database. Together, they cover more than 800 indicators and span 40 years. The 208 pages of country tables in the LDB present the latest available data for World Bank member countries and other economies with populations of more than 30,000. The 14 summary pages cover aggregate data for regional and income groups. The data in this book are for 1990, 2003, and 2004 or the most recent year available unless otherwise noted in the glossary: i) growth rates are proportional changes from the previous year unless otherwise noted; ii) regional aggregates include data for low- and middle-income economies only; and iii) data in italics are for years or periods other than those specified. In keeping with WDI 2006, this edition of The Little Data Book uses terminology in line with the 1993 system of national accounts. In particular, gross national product (GNP) is replaced by gross national income (GNI).